Um estudo de nano-partículas magnéticas via simulação computacional - Julio Cesar Siqueira Rocha (2011)
In this work we present a computational study of magnetism in nano-scale. We modeled the magnetic properties of nano-particles using a classical spins model defined in a lattice. In our model we consider exchange and dipolar interactions as well. The former acts only betweenfirst neighbors while the latter is long-ranged and must be computed between all the spins on the system. We have discussed alternative models for the dipole term. Our calculations show that the dipolar interactions cannot be approximated by any cutoff in the potential.The influence of the geometry of the nano-particle and the application of external fields in the formation of vortex structures were studied in several situations. We have determined the conditions under which a vortex appears as the ground state of the model and how theirmorphology is affected by the geometry of the nano-particle. Vortex-antivortex pairs appear in the system when the temperature is raised. It is believed that a vortex-antivortex creation and annihilation mechanism is responsible for the polarity switching of the vortex. Our simulations do not give support to this mechanism.We have also studied the behavior of nano-particles in the presence of an external magnetic field. Typical nanostructures hysteresis curves were obtained. The effect of exchange-bias in nano-disks deposited over antiferromagnetic substrates is also considered.